Średniowieczna religijność ludowa: Dualizm w świetle Interrogatio Iohannis = MEDIEVAL FOLK RELIGIOUSNESS : CATHAR DUALISM IN THE LIGHTOF THE INTERROGATIO IOHANNIS - Myszor, Wincenty (Studia religiologica, 2008)
Cathar religiousness was not regulated top-down, by any central institution as in the Church. Distinct, particular forms of religiousness were revealed in respective writings. What united them was dualism, what set them apart was reliance on apocryphal which generally expressed folk attitudes in medieval religiousness. A more systematic approach to Cathar teachings is better seen in accounts by Church polemics than in original Cathar writings. Medieval religiousness manifested itself in the apocryphal Interrogatio Iohannis. The text was used by Bogomils and Cathars alike. The dualism in the Interrogatio is not as radical as anti-Cathar polemics show it. In the Interrogatio, it is seen in an opposition between Christ, the Son of God, and satan, also „a son of God.” Satan created the world by the consent of God, his Father. Dualism was also marked in rigorous attitudes toward marriage and material goods. The Cathars of the Interrogatio Iohannis rejected institutional Church and its sacraments, baptism and the Eucharist, attributing to them a spiritualistic or eschatological sense. The folk origin of the text’s character reveals influences of apocryphal literature, but also of Church teaching and New Testament themes, including those opposed to Cathar logic.